Weaving. : Contemporary makers on the Loom. - Treggiden, Katie (Antwerpen : Ludion, 2018)
Clements, Dee ; Takeda, Hiroko ; Griffiths, Genevieve ; Van Dijck, Hermine ; Kehayoglou, Alexandra ; Harris, Daniel ; Carlander, Karin ; Riley, Erin ; Chang, Lauren ; Aguiniga, tanya ; Scott, Rachel ; Just, Judit ; Wadden, Brent ; Snack, Rachel ; Dekker, Diendke ; Matson, Christie ; Pritchard, Eleanor ; Keane, Jen ; Acke, Ilse ; Mattes, Kayla ; Rousseau, Allyson
weven, tapijtkunst
boek